Application And Relevancy Of Anatomy Curriculum In The Clinical Years: A Malaysian University Experience - Rani Sakaran; Noor Azzizah Omar; Sharifa Abdul Aziz; Normaliza Omar; Suhaila Sanip; Ku Mastura Ku Mohd Noor; Mohd Hairulhisyam Ngatiman; Nadeeya'ayn Umaisara Mohamad Nor (Penerbit Universiti Sains Malaysia, 2024)
Indexed by SCOPUS/MYCITE